"Turn-on" fluorescence sensor for organic amines fabricated via sustainable processing. (30th November 2022) - Hu, Renjian; Lin, Shiyun; Hu, Danning; Huang, Hongye; Wang, Mengshi; Li, Ruoxin; Tian, Mei; Shuai, Zhigang; Wei, Yen
Abstract : A broad-spectrum "turn-on" fluorescent sensor for organic amines has been established with a bis-catechol-decorated naphthalene scaffold. It is first synthesized through green chemistry processing with lower solvent consumption. Abstract : The detection of organic amines is a pivotal issue in chemistry. Here we present the synthesis of a novel fluorescence probe with "turn-on" greenish emissive (486 nm) response towards a series of organic amines for the first time with di-catechol moiety-based sensing materials. This sensor was fabricated from a 1, 5-disubstituted naphthalene scaffold that was prepared via a sustainable process without the use of column chromatography or recrystallization. We reveal its dual-mode sensing capability covering visual and quantitative recognition for organic amines with a detection limit down to sub-ppm level. This system may find a broad spectrum of potential applications for monitoring organic amines in various fields, such as bioscience, biomedicine, pharmaceuticals, food science and environmental chemistry.